2021
DOI: 10.48550/arxiv.2111.04002
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Certifying beyond quantumness of locally quantum no-signalling theories through quantum input Bell test

Abstract: Physical theories with local structure similar to quantum theory can allow beyond-quantum global states that are in agreement with unentangled Gleason's theorem. In a standard Bell experiment any such bipartite state produces correlations that are always quantum simulable. In this limited classical-input-classical-output Bell scenario, we show that there exist bipartite beyond-quantum states that produce correlations all of which are in-fact classically simulable. However, if the type of Bell scenario is gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 30 publications
(68 reference statements)
0
4
0
Order By: Relevance
“…More recently, this scenario has been further generalized where Alice and Bob are given quantum inputs instead of classical random variables. [70][71][72].…”
Section: Bell Scenariomentioning
confidence: 99%
“…More recently, this scenario has been further generalized where Alice and Bob are given quantum inputs instead of classical random variables. [70][71][72].…”
Section: Bell Scenariomentioning
confidence: 99%
“…In this work, we assume subsystems to be quantum and ask how the information processing capabilites of composite systems change when one uses different mathematical structures to describe composition. While Barnum,et al in [20] have shown that in the space-like scenario, bipartite maximal tensor product structure of local quantum systems cannot generate beyond quantum correlations, the authors in [22] have shown that in a generalized Bell scenario every beyond quantum state can produce beyond quantum correlations. In this work, we have used a different approach wherein timelike scenarios are considered instead of the traditional spacelike Bell scenarios.…”
Section: Theorem 3 the Information Dimension Of The Systemmentioning
confidence: 99%
“…While maximal composition involving more than two subsystems can yield stronger than quantum correlation in typical Bell scenario [21], recently in Ref. [22] it has been shown that even in bipartite case stronger than quantum correlations are possible if the typical classical input-classical output Bell scenario is generalized to quantum input-classical output semi-quantum scenario [23]. Although this quantum input scenario disallows all the compositions having beyond entangled states it requires trustworthy verifiers in producing some predetermined unentangled quantum inputs [22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation